2019
DOI: 10.1186/s12881-019-0928-2
|View full text |Cite
|
Sign up to set email alerts
|

COL5A1 rs12722 polymorphism is not associated with passive muscle stiffness and sports-related muscle injury in Japanese athletes

Abstract: BackgroundPoor joint flexibility has been repeatedly proposed as a risk factor for muscle injury. The C-to-T polymorphism (rs12722) in the 3′-untranslated region of the collagen type V α1 chain gene (COL5A1) is reportedly associated with joint flexibility. Flexibility of a normal joint is largely determined by passive muscle stiffness, which is influenced by intramuscular collagenous connective tissues including type V collagen. The present study aimed to test the hypothesis that the COL5A1 rs12722 polymorphis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…This data suggest that T allele is involved in the synthesis of more type V collagen α1 chain than other polymorphism, resulting in changes in the mechanical properties of the connective tissue [48]. In this study patients with TT genotype showed a ROM of passive external rotation statistically significantly lower compared to other analyzed genotypes, supporting the hypothesis that the T allele of the COL5A1 rs12722 polymorphism is associated with high muscle stiffness [49]. ClinVar database characterized COL5A1 rs12722 polymorphism as benign (National Center for Biotechnology Information.…”
Section: Discussionsupporting
confidence: 77%
“…This data suggest that T allele is involved in the synthesis of more type V collagen α1 chain than other polymorphism, resulting in changes in the mechanical properties of the connective tissue [48]. In this study patients with TT genotype showed a ROM of passive external rotation statistically significantly lower compared to other analyzed genotypes, supporting the hypothesis that the T allele of the COL5A1 rs12722 polymorphism is associated with high muscle stiffness [49]. ClinVar database characterized COL5A1 rs12722 polymorphism as benign (National Center for Biotechnology Information.…”
Section: Discussionsupporting
confidence: 77%
“…While three studies also included children, their results obtained in adult subjects met our inclusion criteria 26,37,38 . Eleven studies included men exclusively, 22–29,33,37,38 one study only females 31 and five both genders 30,32,34–36 . A summary of the study characteristics is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies assessed the link between genetic polymorphisms and NCMI risk (injured subjects vs. non‐injured subjects), 30–37 eight studies between genetic polymorphisms and NCMI incidence, 22–27,36,38 12 between genetic polymorphisms and injury severity, 22–29,35–38 and three between genetic polymorphisms and recovery time 22,27,28 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific mechanism by which the rs1107946 polymorphism influences the observed muscle phenotypes in females remains unclear. However, sex differences have been reported in joint flexibility and muscle stiffness ( 38 , 39 ), wherein females exhibit greater joint flexibility and lower muscle stiffness than males. These differences may be related to sex hormones such as estrogen.…”
Section: Discussionmentioning
confidence: 99%